Changes in three of the four coat proteins of oral polio vaccine strain derived from type 1 poliovirus. - Kew, O M (1980)
Little is yet known about the nature, or extent, of the changes involved in attenuation of neurovirulent poliovirus. The tryptic comparison reported here, of coat proteins from the Sabin type 1 polio vaccine and parental Mahoney virus, provides a useful approach and affords some insight into this question. The main obstacle, separation of the labile proteins VP1 and VP2 in an intact state from the vaccine strain, was overcome by incorporating 3.5 M urea into an otherwise standard preparative gel electrophoresis system. Tryptic maps revealed six altered leucine-containing peaks: two in VP1, none in VP2, three in VP3, and one in VP4. It is estimated, after correcting for leucine-free peptides, that the coat protein sequences may have undergone some 10 to 13 amino acid replacements, roughly 1.5% of the total, in the course of attenuation leading to the vaccine strain.